Eksistensi Pemerintahan Negeri Waraka dalam Sistem Pemerintahan Indonesia Berbasis Adat - Piere A.L Lailossa (PT. Hasba Edukasi Mandiri, 2026)
This research is motivated by the continued existence of customary village governance in Indonesia amid the dominance of the state legal system, particularly in Maluku where customary villages are known as Negeri. The research problem focuses on the legal position of customary village governance within the Indonesian governmental system and the existence of the Waraka Negeri Government in exercising its authority based on customary law and national law. The purpose of this study is to analyze the legal status of customary villages within Indonesia’s constitutional framework and to examine the sustainability of the Waraka Negeri Government as an adat-based governance system. This study employs a normative juridical research method with a doctrinal approach, utilizing library research on primary, secondary, and tertiary legal materials. The findings indicate that the Waraka Negeri Government possesses dual legitimacy: customary legitimacy derived from original rights and juridical legitimacy through formal legal recognition, particularly under the 1945 Constitution of the Republic of Indonesia, Law Number 6 of 2014 on Villages, and Central Maluku Regency Regulation Number 1 of 2006 on Negeri. The study concludes that the Waraka Negeri Government continues to exist and function effectively within Indonesia’s governmental system, and that regulatory reinforcement and harmonization between customary law and state law are essential to ensure the sustainability of customary village governance.